Application of Proniosomal Powder Technology to Prepare Fast Water Dissolving Tablets for Dutasteride - Nidhal K. Maraie (Journal of Global Pharma Technology, 2018)
Objective: The aim of the study is to prepare fast water dissolving dutasteride tablets containing a pronisomal powder that yield niosomal dispersion of dutasteride upon dissolving in hot water. The niosomes derived from dissolved tablets may improve the dissolution and permeability of dutasteride since it is loaded in the niosomal vesicles and avoid the high cost and other disadvantages of the soft gelatin capsules commercially available. Method: Ten formulas of dutasteride proniosomal gels were prepared by coaservation method and niosomes derived from them were evaluated for their loading capacity, particle size, particle size distribution , zeta-potential and in-vitro drug release in order to determine the optimum type and quantity of proniosomal contents that will be used to prepare maltodextrin based proniosmal powder formulas which were evaluated and the optimum proniosomal powder formula was used to prepare dutasteride tablet. Results: Thickness, , hardness, disintegration time and in-vitro drug release for the optimum dutasteride tablet T5 were 5.57±0.08 mm, 3.1±0.11 Kg/cm2, 2.9±0.03 and reaches 100% release after 30 min. Particle size, polydispersity index (PDI), and zeta potential of niosomes derived from dissolving dutasteride tablet (T5) were 263±3.8 nm, 0.225, and -5.43±0.436 mV Conclusion: This results indicating the contribution niosomes derived from proniosomal powder in improving the dutasteride solubility and gave higher dissolution rate compared to the conventional soft gelatin capsule of the same drug . Therefore presenting an oral dosage form that is more convenient and having all the advantage of tablets. Keywords: Cholesterol, Dutasteride, Niosomes, Proniosomes, Span 60, and Tween 20.